Pengaruh Free Cash Flow terhadap Financial Distress Melalui Profitabilitas dan Leverege - Anggita Septiarni; Marhaendra Kusuma; Dewi Wungkus Antasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the effect of free cash flow on financial distress through return on assets and debt to assets ratio in the pharmaceutical subsector listed on the Indonesia Stock Exchange (BEI) during the period of 2020-2023. The analytical methods employed include descriptive analysis, correlation analysis, classical assumption testing, multiple linear regression analysis, and path analysis. The tool used for analysis is SPSS Version 25. The population consists of 13 companies, and through purposive sampling, a sample of 10 companies was obtained, resulting in a total of 40 firm observations over the 4-year period. The findings indicate that free cash flow has a negative effect on financial distress. Additionally, free cash flow positively influences both return on assets and debt to assets ratio. Return on assets has been proven to mediate the effect of free cash flow on financial distress, while debt to assets ratio does not demonstrate significant mediating capability. The originality of this research builds upon previous studies by introducing return on assets as a moderating variable and also incorporates debt to assets ratio as a moderating variable in the analysis.